Silence and sound theories of poetics from the eighteenth century - Bradford, Richard 1957- (Fairleigh Dickinson Univ. Press [u.a.], 1992)
Reading poems silently and reading them aloud involve two separate dimensions of understanding, and unless we accept that "silent poetics" and spoken performance create tensions and ambiguities that can only be resolved through the readers' control of both experiences, we will perpetuate an inaccurate perception of how poetry works. Such a challenge to the traditional communicative priorities of speech and writing is probably familiar to readers of concrete poetry and poststructuralist theory, but it occurred, with startling consequences, in the work of a number of eighteenth-century critics. These writers found themselves dealing with a poetic "tradition" barely 150 years old, and they lacked a single methodology or code of interpretation through which they might deal with the complex relation between structure and effect
Keywords: Geschichte 1700-1800; Geschichte 1640-1825; Geschichte 1700-1930; Dichtkunst; Engels; Englisch; Geschichte; English poetry -- History and criticism -- Theory, etc; English poetry -- 18th century -- History and criticism -- Theory, etc; Poetics -- History -- 18th century; Hören; Schriftbild; Versdichtung; Prosodie; Lesen; Lyrik; Poetik; Klang; Großbritannien